Uncontrolled severe T2 asthma: Which biological to choose? A biomarker-based approach - López-Viña, Antolín; Díaz Campos, Rocío M.; Trisan Alonso, Andrea; Melero Moreno, Carlos (Frontiers in Allergy, 2022)
In recent years, advances in knowledge of molecular mechanisms involved in asthma have changed uncontrolled severe asthma (USA) treatment, with the appearance of biological treatment. USA is a heterogeneous entity with different endotypes and phenotypes. Nowadays, the biological drugs approved with asthma indication are omalizumab, mepolizumab, reslizumab, benralizumab and dupilumab. Tezepelumab is approved by the Food and Drug Administration (FDA) in the United States and, recently, by the European Medicines Agency (EMA). All these biological drugs have shown their efficacy in clinical trials, especially in reducing exacerbations, improving asthma control, quality of life, pulmonary function, and withdrawing systemic corticosteroids or at least reducing their daily dose, with some differences between them. Except for mepolizumab and reslizumab, biological drugs have different targets and thus different therapeutic indications should be expected; however, in some patients, more than one drug could be indicated, making the election more difficult. Because there are no direct comparisons between biological drugs, some biomarkers are used to choose between them, but they are not unbeatable. In this article, an algorithm to choose the first biological drug in a specific patient is proposed based on different study results and patient’ characteristics.